To investigate the contribution of sports performance inventory in Athlete performance as a psychological measure - Ayesha Mussarrat, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
The purpose of this study is to determine the role of sports performance inventories in athlete performance by incorporating the athlete’s emotional control, team orientation, positive attitude, competitiveness, and mental toughness. Indeed, athletes face exterior challenges and internal ones that impair their performance. This study is cross-sectional and utilizes a questionnaire to collect quantitative data. The sample size for this study was 780, based on a response rate of 45% among the respondent population of Jordanian athletes. This study finds that the psychological measures of athlete emotional control, team orientation, and positive attitude have a critical role in improving athletes’ competitiveness and performance. This study is notable because it explored the psychological measures used to collect data from respondents to comprehend the relationship established in the theoretical framework for examining their involvement in athlete performance. Additionally, this work has substantial theoretical and practical implications for athletes seeking to better their performance.